Characterization of the Powdery Mildew Resistance Gene in the Elite Wheat Cultivar Jimai 23 and Its Application in Marker-Assisted Selection - Jia, Mengshu; Xu, Hongxing; Liu, Cheng; Mao, Ruixi; Li, Haosheng; Liu, Jianjun; Du, Wenxiao; Wang, Wenrui; Zhang, Xu; Han, Ran; Wang, Xiaolu; Wu, Liru; et al. (Frontiers in Genetics, 2020)
Wheat (Triticum aestivum L.) powdery mildew, caused by Blumeria graminis f. sp. tritici (Bgt), is a destructive disease that threatens yield and quality worldwide. The most effective and preferred means for the control of the disease is to identify broad-spectrum resistance genes for breeding, especially the genes derived from elite cultivars which have desirable agronomic performance. Jimai 23 is an Chinese wheat cultivar with superior agronomic performance and high quality character. It shows effective resistance to powdery mildew at the whole growth stages. Genetic analysis using different Bgt isolates indicated that the powdery mildew resistance (Pm) in Jimai 23 was mediated by a single dominant gene, tentatively designated PmJM23. Using bulked segregant RNA-Seq (BSR-Seq), a series of markers were developed and used to map PmJM23. PmJM23 was then located at the Pm2 locus on the short arm of chromosome 5D (5DS). Resistance spectrum analysis demonstrated that PmJM23 provided broad resistant spectrum and different from that of the documented Pm2 alleles, indicating that PmJM23 is most likely a new allele of Pm2. In view of the combined broad-spectrum resistance of PmJM23 and the superior agronomic performance and high quality character of the donor, PmJM23 is expected to be a valuable resistance gene in wheat breeding. To efficiently use PmJM23 in breeding, the closely linked markers of PmJM23 were evaluated and confirmed to be applicable for marker-assisted selection (MAS). Using these markers, a series of resistant breeding lines with high resistance and desirable agronomic performance have been selected from the crosses involving PmJM23, which improved the powdery mildew resistance of these lines.